04.08 Members of the type 14 c-type lectin family protect from inflammatory arthritis but differentially regulate bone erosions. (1st March 2017) - Naylor, Amy; Wehmeyer, Corinna; Croft, Adam; Khan, Kabir; Saghir, Atif; Bicknell, Roy; Buckley, Christopher
Abstract : Background: The type 14 family of C-type lectins has four members, two of which have very similar structures: Endosialin is expressed on stromal cells (including osteoblasts, fibroblasts and pericytes) and upregulated in rheumatoid arthritis; 1 clec14a is expressed on endothelial cells and osteoblasts. Both endosialin and clec14a have been extensively studied in cancer where they are expressed on tumour pericytes and endothelial cells respectively and are required for sprouting angiogenesis. 2–5 Here we have investigated the effect of genetic deletion of endosialin or clec14a on inflammatory arthritis. Materials and methods: KBxN serum-transfer arthritis was used to study the effect of genetic deletion of either endosialin or clec14a on mouse arthritis progression. Staining for tartrate-resistant alkaline phosphatase was used to quantify osteoclast number. MicroCT and histology were used to assess bone erosion. Osteoblast-osteoclast co-cultures were used to identify the relative roles for each of these cell types in bone erosion. RANKL and OPG were measured at the mRNA and protein levels. Results: Both endosialin and clec14a-deficient ( -/- ) mice show an increase in arthritis severity (increased duration of disease and increased swelling) compared to wildtype. MicroCT data demonstrated that, despite their increased paw swelling, clec14a -/- mice had levels of bone erosion similar to wildtype mice. In contrast, bone erosion in endosialin -/- mice was severe and extensive and histology identified a 3-fold increase in osteoclast number compared to wildtype. Co-culture experiments identified that endosialin-deficient osteoblasts (but not osteoclasts) stimulated osteoclastogenesis. No effect on the known osteoblast-osteoclast coupling factors RankL and OPG was identified. Conclusions: Here we have identified two members of a protein family, with the same ligand but different cellular expression, which appear to protect against inflammation. However, underlying these apparently similar phenotypes we saw a severe bone-erosion defect in endosialin -/- animals that was not present in the clec14a -/- animals. In vitro experiments confirmed a role for endosialin in osteoblast-mediated osteoclastogenesis. These data demonstrate an unexpected disconnection between inflammation and bone damage and imply a novel osteoblast-osteoclast coupling mechanism that warrants further investigation. References: Maia, et al. CD248 and its cytoplasmic domain. A therapeutic target for arthritis. Arthritis and Rheumatism.2010;62: 3595-606. Mura, et al. Identification and angiogenic role of the novel tumour endothelial marker CLEC14A. Oncogene, 2012;31, 293-305. Noy, et al. Blocking CLEC14A-MMRN2 binding inhibits sprouting angiogenesis and tumour growth. Oncogene, 2015;34, 5821-31. Noy, et al. Sprouting angiogenesis is regulated by shedding of the C-type lectin family 14, member A (CLEC14A) ectodomain, catalysed by rhomboid-like 2 protein (RHBDL2). FASEB J. 2016;30, 2311-23. Naylor, et al. A Differential Role for CD248 (Endosialin) in PDGF-Mediated Skeletal Muscle Angiogenesis. PLOS One. 2014;9: e107146